2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6090402
|View full text |Cite
|
Sign up to set email alerts
|

Technical accuracy of an O-arm registered surgical navigator

Abstract: The objective of this study was to assess the accuracy of a commercial surgical navigator using optical tracking modality with automated registration between O-arm images and the scanned object. Automated registration was enabled by using the spine navigation software of the navigator. The used phantom was designed by the authors of this paper. The surgical navigators and the O-arm are routinely used at Oulu University Hospital, Oulu, Finland. The distances measured with the surgical navigator from the fixed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…In more recent years, the development of new intraoperative devices able to perform 3D imaging has become the focus of attention, especially in spine surgery. In fact, the advent of a cone beam-based imaging system (O-arm system, Medtronic, Inc.), especially when associated with an image-guided system (IGS), was seen as a revolution, 17 and excellent results were reported, 3,9,10,13,21,22,27 with accuracy in screw placement up to 98.5%. 4 However, despite these encouraging results there is still debate regarding where and when this technology should be used.…”
mentioning
confidence: 99%
“…In more recent years, the development of new intraoperative devices able to perform 3D imaging has become the focus of attention, especially in spine surgery. In fact, the advent of a cone beam-based imaging system (O-arm system, Medtronic, Inc.), especially when associated with an image-guided system (IGS), was seen as a revolution, 17 and excellent results were reported, 3,9,10,13,21,22,27 with accuracy in screw placement up to 98.5%. 4 However, despite these encouraging results there is still debate regarding where and when this technology should be used.…”
mentioning
confidence: 99%
“…This is especially useful in axial locations that are deep or difficult to palpate (see Appendix). Intraoperative three-dimensional imaging simultaneous with navigation overcomes the problem of time separation between CT imaging and insertion of the Kirschner wire or probe, and it is more accurate than using paired points and surface-matching techniques 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The safety profile of electrode implantation with 3D DSA guidance is excellent, likely due to the detailed visualization of the cerebrovasculature and the low distortion inherent with CT scanning (12,23,25). In a previous study (10) we reported our first 81 cases of SEEG implantations based on our 3D DSA technique, without any major intracranial bleedings and only two minor ones.…”
Section: D Dsa With O-arm For Seegmentioning
confidence: 86%